The Economic Impact of Cutaneous Leishmaniasis in Sri Lanka - Wijerathna, Tharaka (Biomed Res Int, 2018)
Cutaneous leishmaniasis (CL) is a neglected tropical disease which affects mainly the poorest communities in developing countries. Considering the limited published information on economic impact of CL in Sri Lanka, the current study was conducted with the objective of revealing the nature and magnitude of the economic impact of CL in three selected disease endemic regions in Kurunegala District, Sri Lanka. The patient records of CL notified of relevant Medical Officer of Health (MOH) office during 2013- 2016 were obtained. Patient households were visited and data collection was done using an interviewed administered questionnaire. The majority of patients (57%) were economically active at the time of infection. Of them, 65% were the only contributors to household economy. Total median costs including both direct and indirect costs were 66.85 USD (Rs. 10,831) (IQR = 57.26 - 86.78 USD), while total median economic loss to households was 61.27 USD (Rs. 9,927) (IQR= 49.61- 75.04 USD). From provider perspective, total median cost per patient was 22.83 USD (Rs. 3,696). The mean total economic loss was denoted as 65.26 USD (Rs. 10,572) which is about 5.4% of the annual household income and 20.9% of the mean annual per capita income of the study population. Although economic impact of CL infection is not catastrophic according to current interpretation, the infection may have significant economic impacts on households when considering the mean economic loss to household as a percentage of the mean annual per capita income of the population.